Abnormal singing can identify patients with right hemisphere cortical strokes at risk for impaired prosody. Issue 23 (11th June 2021) - Lin, Rebecca Z.; Marsh, Elisabeth B.
Abstract : Abstract: Despite lacking aphasia seen with left hemisphere (LH) infarcts involving the middle cerebral artery territory, right hemisphere (RH) strokes can result in significant difficulties in affective prosody. These impairments may be more difficult to identify but lead to significant communication problems. We determine if evaluation of singing can accurately identify stroke patients with cortical RH infarcts at risk for prosodic impairment who may benefit from rehabilitation. A prospective cohort of 36 patients evaluated with acute ischemic stroke was recruited. Participants underwent an experimental battery evaluating their singing, prosody comprehension, and prosody production. Singing samples were rated by 2 independent reviewers as subjectively "normal" or "abnormal, " and analyzed for properties of the fundamental frequency. Relationships between infarct location, singing, and prosody performance were evaluated using t tests and chi-squared analysis. Eighty percent of participants with LH cortical strokes were unable to successfully complete any of the tasks due to severe aphasia. For the remainder, singing ratings corresponded to stroke location for 68% of patients. RH cortical strokes demonstrated a lower mean fundamental frequency while singing than those with subcortical infarcts (176.8 vs 130.4, P = 0.02). They also made more errors on tasks of prosody comprehension (28.6 vs 16.0, P < 0.001) and production (40.4 vs 18.4, P < 0.001). Patients with RH cortical infarcts are more likely to exhibit impaired prosody comprehension and production and demonstrate the poor variation of tone when singing compared to patients with subcortical infarcts. A simple singing screen is able to successfully identify patients with cortical lesions and potential prosodic deficits.